How Often Do Pauses Occur in Lexical Bundles in Spoken Native English Speech? - Flinn, Andrea (Corpus pragmatics : international journal of corpus linguistics and pragmatics, 2023)
The frequency of pauses in phraseological units has been the subject of previous research because it could shed light on how linguistic information is stored in and retrieved from the mind. This previous research was grounded in earlier findings that pauses reflect the exertion of cognitive effort when performing a lexical search. The current study examines the frequency of pauses in native English speech from the prosodically annotated Hong Kong Corpus of Spoken English (Cheng et al. in ICAME J 29:44–48, 2005). Specifically, the study examines the frequency of pauses inside four-word lexical bundles. Moreover, it notes clause boundaries within such four-word bundles which coincide with pauses. Results show that only one percent of pauses fell within the bundles. The functional and structural characteristics of bundles containing pauses are investigated using the framework introduced by Biber et al. (Appl Linguist 25(3):371–405, 2004), specifically those conveying either epistemic stance or imprecision, or those organizing the discourse. Results highlight the strengths and limitations of identifying holistically stored multi-word units via frequency, and suggest steps for addressing the limitations, including observing when the bundles fall within longer phraseological units. Overall, findings support the suggestion that lexical bundles are holistically stored in and retrieved from the mind, and that frequency-based identification is an efficient tool for identifying holistically stored units that can be strengthened through supplementation.